Expanding banks’ customer base through the adaptation of digital interfaces for low-mobility population groups - Sylyvonchyk, Krystyna (Актуальні питання економічних наук, 2025)
The relevance of this study is determined by the deepening digitalization of the banking sector alongside the persistent structural digital divide between formal access to financial services and their actual use. Despite the high level of development of payment infrastructure and the growing number of remote banking users, a significant proportion of clients, particularly low-mobility and socially vulnerable groups, remain insufficiently integrated into modern financial processes. The purpose of this article is to substantiate the adoption of digital banking interfaces as an instrument for expanding banks’ customer base by overcoming visual, cognitive, and behavioral barriers to digital engagement among low-mobility population groups. The methodological framework of the study is based on scientific generalization, structural and comparative analysis, and the examination of official statistical and analytical materials. The empirical basis of the research is formed using data from the FDIC National Survey of Unbanked and Underbanked Households and the Federal Reserve’s «Report on the Economic Well-Being of U.S. Households in 2024», which made it possible to analyze financial inclusion, the use of alternative financial services, and behavioral patterns of users in the digital environment. The study systematizes the structural components of the digital divide in the banking sector. It demonstrates that the primary loss zone emerges at the stage of transition from formal access and basic digital skills to sustainable digital engagement. It is proven that insufficient interface adaptation intensifies the risks of financial exclusion and contributes to the formation of a segment of passive users. Based on the research findings, an original mechanism for expanding banks’ customer base is proposed, which provides for inclusive adaptation of digital interfaces aligned with the principles of universal design, personalized interaction, and the development of supportive services within digital channels. The practical significance of the obtained results lies in their applicability for banking institutions in improving the efficiency of digital service channels, stimulating the use of financial services by low-mobility population groups, and ensuring sustainable growth of the customer base under conditions of digital transformation.